SITUS SEJARAH PEREKAT KERUKUNAN DAN MAKNANYA DALAM KEHIDUPAN BERBANGSA DAN BERNEGARA - Ida Bagus Brata; Ruli Anto; Ida Bagus Wartha; Adi Saputra (Jurnal Pendidikan, 2021)
This study tries to examine the role of historical sites as the glue of national harmony amidst problematic security. History is the result of the reconstruction of past human creations, feelings, initiatives, and works, but how to position historical sites so that they continue to play a role in the future of a nation. Historical sites contain various emotions in them that must be narrated. History awakens the realization of the dimensions of space and time which are essential in human existence. This research was designed qualitatively with a natural approach, supported by literature studies, by placing the researcher as the key instrument. Sampling was purposive, data collection was carried out by triangulation techniques, data analysis was interpretive qualitative. The results of the research show that the use of historical sites as learning resources and connecting media is something very strategic in the midst of the dynamics of society that leads to barrier-free. Historical sites can act as a medium that connects the present with the past. Historical sites can be used as symbols of the glue of national harmony. As a symbol of harmony, historical sites contain symbolic, informative, aesthetic, and economic values and meanings in an effort to build a better future for the nation.